E-Stilbenes: General Chemical and Biological Aspects, Potential Pharmacological Activity Based on the Nrf2 Pathway - Elaine L. S. S. Mendonça; Jadriane A. Xavier; Marilene B. T. Fragoso; Messias O. Silva; Pierre B. Escodro; Alane C. M. Oliveira; Paolo Tucci; Luciano Saso; Marília O. F. Goulart (MDPI AG, 2024)
Stilbenes are phytoalexins, and their biosynthesis can occur through a natural route (shikimate precursor) or an alternative route (in microorganism cultures). The latter is a metabolic engineering strategy to enhance production due to stilbenes recognized pharmacological and medicinal potential. It is believed that in the human body, these potential activities can be modulated by the regulation of the nuclear factor erythroid derived 2 (Nrf2), which increases the expression of antioxidant enzymes. Given this, our review aims to critically analyze evidence regarding E-stilbenes in human metabolism and the Nrf2 activation pathway, with an emphasis on inflammatory and oxidative stress aspects related to the pathophysiology of chronic and metabolic diseases. In this comprehensive literature review, it can be observed that despite the broad number of stilbenes, those most frequently explored in clinical trials and preclinical studies (in vitro and in vivo) were resveratrol, piceatannol, pterostilbene, polydatin, stilbestrol, and pinosylvin. In some cases, depending on the dose/concentration and chemical nature of the stilbene, it was possible to identify activation of the Nrf2 pathway. Furthermore, the use of some experimental models presented a challenge in comparing results. In view of the above, it can be suggested that E-stilbenes have a relationship with the Nrf2 pathway, whether directly or indirectly, through different biological pathways, and in different diseases or conditions that are mainly related to inflammation and oxidative stress.